Follow-up visits to check strings after intrauterine contraceptive placement cannot predict or prevent future expulsion. (4th March 2019) - Bahamondes, Luis; Monteiro, Ilza; Fernandes, Arlete; Gaffield, Mary E.
Abstract: Objectives: In some settings women are advised to return to the clinic after intrauterine contraceptive (IUC) placement, for a follow-up visit to check the strings and identify any expulsions. Our objective was to evaluate whether the number of follow-up visits to check the strings at the external cervical os after IUC placement predicts or prevents future expulsions. Methods: This was a retrospective study conducted at the University of Campinas Medical School, Brazil. We reviewed the medical records of all women who used an IUC between January 1980 and December 2017, to identify women who had experienced IUC expulsion ( N  = 1974). We excluded women whose IUC was expelled more than once ( n  = 331) or after 10 years of use ( n  = 31). We fitted a generalised linear model of the time between IUC placement and expulsion, adjusting for several variables at expulsion. Significance was established at p  < .05. Results: Most expulsions (843/1612; 52.3%) occurred within the first 6 months after IUC placement and 691/1612 (42.9%) were within the first three months after placement. The adjusted model showed that the number of visits, the woman's age, and complaints of pain and bleeding during use were not significantly associated with and had no influence on expulsion. Conclusions: Our results indicate that after IUC insertion more than one follow-up visit within the first four to six months after placement is not necessary, as additional visits to check for IUC strings do not appear to reduce or predict future expulsion.